Modelling Multiple Dosing with Drug Holiday in Antiretroviral Treatment on HIV-1 Infection - Sutimin, Sutimin; Nuraini, Nuning; Chirove, Faraimunashe; Suromo, Lisyani Budipradigda (Journal of Mathematical and Fundamental Sciences, 2017)
A within-host mathematical model to describe the dynamics of target cells and viral load in early HIV-1 infection was developed, which incorporates a combination of RTI and PI treatments by using a pharmacokinetics model. The local stability of uninfected steady state for the model was determined using an alternative threshold. The pharmacokinetics model was employed to estimate drug efficacy in multiple drug dosing. The effect of periodic drug efficacy of pharmacokinetic type on outcome of HIV-1 infection was explored under various treatment interruptions. The effectiveness of treatment interruption was determined according to the time period of the drug holidays. The results showed that long drug holidays lead to therapy failure. Under interruption of treatments combining RTI and PI therapy, effectiveness of the treatment requires a short duration of the drug holiday.